Educational Values in the Symbolic Meaning of the Baharin Traditional Ceremony among the Meratus Dayak Community in Mantuyan Village, Halong District, Balangan Regency - Lastaria; Irni Cahyani; Erni Susilawati; Milawati; Ahmad Syarif (Jurnal Hadratul Madaniyah, 2026)
This study examines the symbolic meaning in the traditional ceremony of the Dayak Maratus tribe which aims to describe the meaning and symbols used in the traditional ceremony of Baharin Dayak Meratus in Mantuyan Village, Halong District, Balangan Regency. This study uses a literary semiotic approach to systematically examine knowledge about signs or symbols, symbols, and the process of creation. The type of research is qualitative with descriptive method. The subjects in this study were people or community leaders who had experience or knowledge of Dayak traditional ceremonies in Mantuyan Village. The data collection technique in this study is a data reduction technique as an effort to process the focus of the study, abstracting, transforming data, and presenting data from the process of collecting and organizing. The results of this study are classified into two parts, namely the classification of meanings and symbols in the Baharin traditional ceremony. From the results of customary symbols there are two parts, namely: (a) Verbal symbols there are thirteen discussions, and (b) Non-verbal symbols have six discussions. Judging from the results of the meaning of verbal and non verbal symbols in the traditional ceremony of Baharin Dayak Meratus, 19 discussions.